(untitled) (Revista Brasileira Multidisciplinar, 2019)
This article focuses on the study of the socio-spatial dynamics of vulnerable areas, in order to produce alternatives that aim at improving the quality of life of its residents, since these areas are affected by poverty, violence, diverse risks, among other determinants, as well as being areas that are not constantly included in municipal urban planning plans. Thus, it is necessary to study the socio-spatial dynamics of these areas through the urban planning bias. For this purpose, the case of the neighborhood of Cristo Rei, located in the city of Montes Claros / MG, was studied, since the city is of medium size and has great socioeconomic importance for the north of Minas Gerais. The Cristo Rei City neighborhood is located in the central region of the city and has a subnormal cluster within its boundaries, which makes it an even more vulnerable area. The approach here is based on the principle of social learning, that is, it seeks different alternatives for the aforementioned neighborhood, which are a product of the dialogue between social interest (popular participation) and public interest (municipal government). Finally, urban planning associated with social learning has proved to be an important research tool capable of bringing together several complex themes about the territory in question and, thus, can point to transforming principles for other vulnerable regions of the city of Montes Claros and the region